Instilling Nationalism Values Through History Learning for Grade XI Students - Suciati, Rahmadiah; Kumalasari, Dyah; Setiawan, Johan (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2023)
The issue of nationalism which is starting to fade among the younger generation is caused by the negative impact of globalization. Learning history is one of the solutions to revitalize the values of nationalism. This study aims to analyze the process of instilling nationalist values in history learning, the obstacles encountered when instilling nationalist values in history learning, and the efforts made in overcoming the obstacles faced by teachers when instilling nationalist values in history learning. Qualitative type research with case studies. The research subjects were madrasa heads, history teachers, and students of class XI IPS. Data collection techniques: observation, interviews, documentation. Data analysis techniques use the Miles & Huberman model. The results of the study show that the process of instilling nationalist values in history learning is through planning, implementing, and evaluating. The obstacles experienced were students' different backgrounds, difficulties in controlling internet use, mass media reporting, and the absence of a history laboratory. Efforts made by the teacher, namely making himself a role model and motivator, holding an agenda for mandatory visits to historical sites, participating in every national holiday commemoration event. The conclusion of instilling the values of nationalism in history learning can be seen from the cognitive, affective, psychomotor aspects of students.